2022
DOI: 10.21744/ijhms.v5n3.1931
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding in family with early marriage

Abstract: Background: Breast milk is the best nutrient for infant, providing everything the babies need to survive and drink plenty of fluids during the first six months and that is perfect combination of various nutrients. Besides that, breast milk is the best way to reduce infant morbidity and mortality from infectious diseases, which often affect toddlers in developing countries who are not getting the appropriate developmental nutrition. Meanwhile, the level of national initiation is checked according to mother’s ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A high level of education was one factor in shaping broad knowledge so that one has broader and more easily informed insight. 8 Although education levels affect one's knowledge, knowledge could still be obtained outside formal education 8 , so that it was not an absolute factor.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of education was one factor in shaping broad knowledge so that one has broader and more easily informed insight. 8 Although education levels affect one's knowledge, knowledge could still be obtained outside formal education 8 , so that it was not an absolute factor.…”
Section: Educationmentioning
confidence: 99%
“…While reinforcement factors include environmental factors, husband/family support, information support, award support, reinforcement, counseling, and media. 8 Studies in Indonesia relate many factors mainly maternal characteristics including age, education, occupations, knowledge, attitudes with exclusive breastfeeding. Age and occupations are found to be associated with exclusive breastfeeding 9 , as well as knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…IVIM assessment in the imaging of several organs has drawn increased attention in recent years, for instance, in the imaging of normal livers and livers with cirrhosis (11)(12)(13)(14) , kidney, (15)(16)(17) , and the prostate (10,18) There was, however, no established technique or ideal set of b-values to distinguish between the diffusion or perfusion effects. Instead, multiple ranges of b-values were employed in the clinical assessment of IVIM characteristics from various institutions (2,19,20) . In clinical settings, the majority of research showed so when b values may be less than 200 s/mm 2 , perfusion also have more dominating effects.…”
Section: Introductionmentioning
confidence: 99%
“…The factor that is a problem in breastfeeding is the lack of breastfeeding intensity so that it affects breast milk production. This is due to the lack of control of the hormone oxytocin which is a hormone that plays a role in the production of breast milk (Darmayanti & Armayanti, 2020;Kadatua et al, 2022). Some studies prove that the work of the hormone oxytocin is influenced by the psychological state.…”
Section: Introductionmentioning
confidence: 99%